2012
DOI: 10.1113/jphysiol.2011.215533
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular BKCa (iBKCa) channels

Abstract: The large conductance calcium-and voltage-activated potassium channel (BK Ca ) is widely expressed at the plasma membrane. This channel is involved in a variety of fundamental cellular functions including excitability, smooth muscle contractility, and Ca 2+ homeostasis, as well as in pathological situations like proinflammatory responses in rheumatoid arthritis, and cancer cell proliferation. Immunochemical, biochemical and pharmacological studies from over a decade have intermittently shown the presence of BK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
140
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(146 citation statements)
references
References 90 publications
(123 reference statements)
3
140
0
1
Order By: Relevance
“…Mechanistically, it seems that 11,12-EET induces the physical association of the BKa and BKb1 subunits on the mitochondrial membrane (Loot et al, 2012). Whether this is a phenomenon exclusive to pulmonary VSMCs remains to be clarified but is of potential interest given that mitochondrial BK channels in the heart are thought to play a role in protection from ischemic injury (for review, see Singh et al, 2012) and both EETs and sEH inhibition protect mitochondrial function after stress (Katragadda et al, 2009;Batchu et al, 2012b).…”
Section: A Calcium-activated Potassium Channelsmentioning
confidence: 99%
“…Mechanistically, it seems that 11,12-EET induces the physical association of the BKa and BKb1 subunits on the mitochondrial membrane (Loot et al, 2012). Whether this is a phenomenon exclusive to pulmonary VSMCs remains to be clarified but is of potential interest given that mitochondrial BK channels in the heart are thought to play a role in protection from ischemic injury (for review, see Singh et al, 2012) and both EETs and sEH inhibition protect mitochondrial function after stress (Katragadda et al, 2009;Batchu et al, 2012b).…”
Section: A Calcium-activated Potassium Channelsmentioning
confidence: 99%
“…3,7,8 Mitochondrial BKCa channel expression has been controversial, presumably because of the low levels of expression and less than optimal available antibodies. BKCa-like currents in mitochondria were first described by Xu et al, who also showed significant cardioprotection using the BKCa activator NS1619 in guinea pig hearts.…”
Section: Expression In the Cardiovascular Systemmentioning
confidence: 99%
“…The observed effect of JAK2 and V617F JAK2 on the large conductance voltage-and Ca 2ϩ -activated K ϩ channels may be relevant for proliferation, migration, and metastasis of tumor cells (15,50,52,54,63,67). However, in some cells other K ϩ channels may functionally replace the BK channels and thus inhibition of BK channels does not necessarily interfere with those functions.…”
Section: Discussionmentioning
confidence: 99%